Long-term prognosis of unrecognized myocardial infarction detected with cardiovascular magnetic resonance in an elderly population. Issue 1 (December 2016) - Barbier, Charlotte; Themudo, Raquel; Bjerner, Tomas; Johansson, Lars; Lind, Lars; Ahlström, Håkan
Abstract Background Individuals with unrecognized myocardial infarctions (UMIs) detected with cardiovascular magnetic resonance (CMR) constitute a recently defined group whose prognosis has not been fully evaluated. However, increasing evidence indicate that these individuals may be at considerable cardiovascular risk. The aim of the present study was to investigate the prognostic impact of CMR detected UMIs for major adverse cardiac events (MACE) in community living elderly individuals. Methods Late gadolinium enhancement CMR was performed in 248 randomly chosen 70-year-olds. Individuals with myocardial infarction (MI) scars, with or without a hospital diagnosis of MI were classified as recognized MI (RMI) or UMI, respectively. Medical records and death certificates were scrutinized. MACE was defined as cardiac death, non-fatal MI, a new diagnosis of angina pectoris, or symptom-driven coronary artery revascularization. Results During follow-up (mean 11 years) MACE occurred in 10 % (n = 18/182) of the individuals without MI scars, in 20 % (n = 11/55) of the individuals with UMI, and in 45 % (n = 5/11) of the individuals with RMI, with a significant difference between the UMI group and the group without MI scars (p = 0.045), and between the RMI group and the group without MI scars (p = 0.0004). Cardiac death and/or non-fatal MI occurred in 15, 5, and 3 of the individuals in the NoMI, UMI, and RMI group respectively. Hazards ratios for MACE adjusted for risk factors and sex were 2.55 (95 % CI 1.20-5.42;p = 0.015) for UMI and 3.28 (95 % CI1.16-9.22;p = 0.025) for RMI. Conclusions The presence of a CMR detected UMI entailed a more than double risk for MACE in community living 70-year-old individuals.